2010
DOI: 10.1071/fp10063
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of growth-promoting plant hormones

Abstract: Abstract. The plant growth hormones auxin, gibberellins (GAs) and brassinosteroids (BRs) are major determinants of plant growth and development. Recently, key signalling components for these hormones have been identified in vascular plants and, at least for the GAs and BRs, biosynthetic pathways have been clarified. The genome sequencing of a range of species, including a few non-flowering plants, has allowed insight into the evolution of the hormone systems. It appears that the moss Physcomitrella patens can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 100 publications
2
40
0
Order By: Relevance
“…Chlorophyta appear to encode at least some of the proteins necessary for auxin biosynthesis and metabolism, which correlates with auxin measurements in members of this division of green algae (Cooke et al, 2002;Lau et al, 2009;Ross and Reid, 2010). On top, putative auxin transport proteins such as AUX1-like and ABCB/PGP-like proteins appear to be present in Chlorophyta, while PIN-like proteins are only encoded in some Streptophyta.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorophyta appear to encode at least some of the proteins necessary for auxin biosynthesis and metabolism, which correlates with auxin measurements in members of this division of green algae (Cooke et al, 2002;Lau et al, 2009;Ross and Reid, 2010). On top, putative auxin transport proteins such as AUX1-like and ABCB/PGP-like proteins appear to be present in Chlorophyta, while PIN-like proteins are only encoded in some Streptophyta.…”
Section: Resultsmentioning
confidence: 99%
“…As summarized recently, various measurements showed that auxin is present in several kingdoms and in a wide range of organisms, including several single-celled and multicellular green algae (Cooke et al, 2002;Lau et al, 2009;Ross and Reid, 2010). Recently, an in silico survey of components of auxin signaling, such as biosynthesis, conjugation, response, and transport, showed that IAA biosynthesis genes from land plants have orthologs in the brown alga Ectocarpus siliculosus Le Bail et al, 2010), and even several bacteria are able to produce auxin (Costacurta and Vanderleyden, 1995).…”
Section: Auxin Biosynthesis and Metabolism In Chlorophytamentioning
confidence: 99%
See 1 more Smart Citation
“…If the mutation affected an earlier step in the somewhat long pathway, then the mutation would have been much less instructive. It turns out also that Mendel's LE gene is regulated by auxin (O'Neill et al 2010;Ross and Reid 2010), another hormone of historical interest, and arguably the most studied of the plant growth substances. Interestingly, even though gibberellins are implicated in a wide range of processes critical for plant yield, including root growth, seed development, and nodulation (e.g., Ferguson et al 2011;Ross et al 2011), Mendel's le-1 mutation has been used in agriculture for many centuries.…”
Section: Stem Lengthmentioning
confidence: 99%
“…A simplified overview of the pathway is presented in figure 1. The number of sequenced lower plant genomes has increased extensively in the past few years, providing opportunities to trace the evolutionary origins of biosynthetic and signaling pathways of plant hormones (Ross and Reid, 2010;Ju et al, 2015). The ethylene biosynthetic pathway, which includes three key enzymes reactions, has been well-documented in higher plants.…”
mentioning
confidence: 99%